The Effect of Pseudo‐Global Warming on the Weather‐Climate System of Africa in a Convection‐Permitting Model - K. M. Núñez Ocasio; Erin M. Dougherty (Geophysical Research Letters, 2024)
Abstract The African easterly jet (AEJ) and the West African Monsoon (WAM) can largely modulate high‐impact weather over Africa and the tropical Atlantic. How these features will change with a warming climate is just starting to be addressed due to global climate model limitations in resolving convection. We employ a novel regional setup for an atmospheric convection‐permitting model alongside the pseudo‐global warming (PGW) approach to address climate change impacts on the weather‐climate system of Africa during a short period of high‐impact weather. Our findings indicate that the AEJ and WAM may intensify in a future warming climate scenario. Precipitation is shown to increase over Guinea Highlands and Cameroon Mountains and shift southward due to a latitudinal expansion and increase of deep convection closer to the equator. This has relevant ramifications for the livelihood of communities that depend on water‐fed crops in tropical Africa.